THE EFFECT OF BILIMBI (BELIMBING WULUH) EXTRACT (Averrhoa bilimbi L) AGAINST DENTAL REMINERALIZATION AND ENAMEL MICROSTRUCTURE (IN VITRO RESEARCH): PENGARUH EKSTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi L) TERHADAP REMINERALISASI GIGI DAN MIKROSTRUKTUR EMAIL (PENELITIAN IN VITRO) - Abidin, Trimurni; Nainggolan, Marline; Susi, Susi (TALENTA, 2017)
Teeth physiologically undergo demineralization and remineralisation processes. One way to reduce demineralization can be done with the use of CPP-ACP (Casein Phosphopeptide-Amorphous Calcium Phosphate), which has high calcium bioavailability. The use of natural materials products in the field of dentistry is currently growing, one of which is bilimbi/ starfruit (belimbingwuluh) that is rich in minerals and has many benefits. This study aims to analyze the effect of extract of bilimbi in tooth enamel remineralisation which is tested by using SEM and EDX equipments so that the difference of enamel surface microstructure and the amount of calcium and phosphorus content of tooth enamel surface can be identified. A total of eight hidden molar teeth were extracted, cut into four parts and divided into four groups, namely group I: the teeth applied with the wuluh bilimbi gel, group II: the teeth applied with CPP-ACP gel, group III: the teeth applied with the combination gel of starfruit extract and CPP-ACP gel, group IV: without any application. The result of this study was assessed qualitatively and it was noticeable that the treatment group combination of CPP-ACP gel and starfruit gel had the smoothest enamel surface microstructure. Quantitatively, there were significant difference is the three treatment groups (pâ‰¤ 0.05). The conclusion of this research is the effect of the application of wuluh bilimbi extract gel, CPP-ACP gel and gel combination of starfruit with CPP-ACP gel towards the remineralisation and microstructure of tooth enamel surface.